Respon Tanaman Sorgum (Sorghum bicolor L. Moench) Terhadap Sistem Tanam Legowo: Program Studi Agroteknologi Fakuktas Pertanian Universitas Tamansiswa Padang - Abdullah, Mahmud Abdullah; Mutia, Yopa Dwi; Zahanis, Zahanis (Jurusan Budidaya Pertanian Fakultas Pertanian Universitas Andalas, 2024)
This experiment aims to determine two sorghum lines that provide the best growth and yield with the legowo spacing system treatment. This experiment was conducted in Kalumbuk Village, Kuranji District, Padang City, West Sumatra from March 2022 - June 2022. The experiment used a Completely Randomized Design (CRD) with 6 treatment combinations and 4 replications, so that 24 experimental units were obtained. The treatment combinations used consisted of control spacing with line 11-1, control spacing with line 76-1, legowo spacing 2:1 with line 11-1, legowo spacing 2:1 with line 76-1, legowo spacing 3:1 with line 11-1, and legowo spacing 3:1 with line 76-1. Based on the experiment, it can be concluded that the combination of the 2:1 jajar legowo planting distance system and the 76-1 line had a significant effect on the observation parameters of plant height, namely 177.9 cm, wet panicle weight, namely 128.33 g, dry panicle weight, namely 82.73 g, and production per hectare, namely 9.49 tons.